2014
DOI: 10.1038/ncomms5371
|View full text |Cite
|
Sign up to set email alerts
|

Taking snapshots of photosynthetic water oxidation using femtosecond X-ray diffraction and spectroscopy

Abstract: The dioxygen we breathe is formed from water by its light-induced oxidation in photosystem II. O2 formation takes place at a catalytic manganese cluster within milliseconds after the photosystem II reaction center is excited by three single-turnover flashes. Here we present combined X-ray emission spectra and diffraction data of 2 flash (2F) and 3 flash (3F) photosystem II samples, and of a transient 3F′ state (250 μs after the third flash), collected under functional conditions using an X-ray free electron la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
166
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 215 publications
(168 citation statements)
references
References 72 publications
2
166
0
Order By: Relevance
“…1b). The high-resolution structures of PSII analyzed so far were for the dark-stable S1 state 4,5 , although a few studies on the low-resolution intermediate S-state structures have been reported by TR-SFX [9][10][11] . During the revision of our manuscript, Young et al reported a 2F-illuminated state structure at 2.25 Å resolution where no apparent changes around O5 were observed 12 , although estimations of the resolution could yield somewhat different values so that small movement of some water molecules may escape the detection.…”
Section: Discussionmentioning
confidence: 99%
“…1b). The high-resolution structures of PSII analyzed so far were for the dark-stable S1 state 4,5 , although a few studies on the low-resolution intermediate S-state structures have been reported by TR-SFX [9][10][11] . During the revision of our manuscript, Young et al reported a 2F-illuminated state structure at 2.25 Å resolution where no apparent changes around O5 were observed 12 , although estimations of the resolution could yield somewhat different values so that small movement of some water molecules may escape the detection.…”
Section: Discussionmentioning
confidence: 99%
“…However, the composition of these protrusions in grana membranes from plants and algae is not completely resolved. The precise locations of PsbP and PsbQ are still uncertain (Ido et al, 2014;Mummadisetti et al, 2014) because only cyanobacterial PSII-OEC crystal structures have been solved (Zouni et al, 2001;Kamiya and Shen, 2003;Ferreira et al, 2004;Loll et al, 2005;Umena et al, 2011;Kern et al, 2013Kern et al, , 2014Kupitz et al, 2014, Suga et al, 2015 and they do not have the PsbP and PsbQ proteins. PsbO is conserved among cyanobacteria, algae, and plants, and its position within PSII-OEC is more certain (Nield and Barber, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, by combining temporally resolved infrared spectroscopy of surface intermediates with monitoring of the electronic structure of the metal oxide surface using ultrafast hard and soft X-ray free electron laser sources will greatly enhance our understanding of these multi-electron catalytic processes. The recent demonstration of timeresolved X-ray emission spectroscopy for elucidating the O 2 -forming step of Nature's water oxidation cycle at the CaMn 4 O 4 cluster of Photosystem II provides an inspiring example of the use of the emerging ultrafast X-ray free electron laser techniques [100]. Such efforts will play a key role in accelerating progress towards efficient metal oxide catalysts for water oxidation, and the coupling to carbon dioxide reduction.…”
Section: Discussionmentioning
confidence: 99%